1992
DOI: 10.1002/ajmg.1320420320
|View full text |Cite
|
Sign up to set email alerts
|

Canine X‐linked muscular dystrophy as an animal model of Duchenne muscular dystrophy: A review

Abstract: Canine X-linked muscular dystrophy is a spontaneously occurring, progressive, degenerative myopathy of dogs that is clinically and pathologically similar to Duchenne muscular dystrophy in man. The molecular basis for the disease has been shown to be a lack of dystrophin, the protein product of the Duchenne muscular dystrophy gene. Breeding colonies of dystrophic dogs have been established. This report reviews the findings of genetic, clinical, pathologic, molecular biologic, and immunocytochemical studies of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
208
6
47

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(273 citation statements)
references
References 22 publications
10
208
6
47
Order By: Relevance
“…47,48 Golden retriever crossbred dogs from a GRMD colony maintained in the Boisbonne Center for Gene Therapy of Oniris, NantesAtlantic College of Veterinary Medicine, Food Sciences and Engineering were studied. Affected dogs, which have progressive clinical dysfunction similar to that of DMD boys, as previously described, 45,49 were initially identified based on PCR-based genotyping, and the pathology confirmed by a dramatic elevation of serum creatine kinase. 50 The animal experiments were approved by the French National Institute for Agronomic Research and were performed according to the guidelines of the Institute.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 Golden retriever crossbred dogs from a GRMD colony maintained in the Boisbonne Center for Gene Therapy of Oniris, NantesAtlantic College of Veterinary Medicine, Food Sciences and Engineering were studied. Affected dogs, which have progressive clinical dysfunction similar to that of DMD boys, as previously described, 45,49 were initially identified based on PCR-based genotyping, and the pathology confirmed by a dramatic elevation of serum creatine kinase. 50 The animal experiments were approved by the French National Institute for Agronomic Research and were performed according to the guidelines of the Institute.…”
Section: Animalsmentioning
confidence: 99%
“…They had an ex vivo multilineage differentiation potential even though they appeared to be committed to the myogenic lineage as evidenced by their ability to spontaneously differentiate into myotubes. In the GRMD dog, which represents the clinically relevant animal model for DMD, 45,46 we showed that MuStem cells can regenerate muscle fibers, allowed dystrophin recovery, and relocated the satellite cell niche. When intra-arterially delivered, they contributed to a partial muscle tissue remodeling with an increase of the fiber regeneration activity and a limitation of the interstitial expansion.…”
mentioning
confidence: 94%
“…102 However, the golden retriever muscular dystrophy has many advantages over the mdx mouse model, including severity of the disease resulting in early death, development of fibrosis and contractures, and homologous immune system. 103,104 The predictive value of outcome measures in these various animal models for human disease is unknown, and essentially unknowable, until there have been enough clinical successes of agents for muscle disease to take from the bedside back to the laboratory.…”
Section: Lack Of Validated Animal Modelsmentioning
confidence: 99%
“…17,18 By contrast, newborn CXMD dogs have a severe progressive course and clinical signs similar to DMD. 19 In DMD and CXMD, skeletal muscle shows early fiber necrosis and regeneration, associated with perimysial and endomysial connective tissue proliferation. 20,21 CXMD is therefore a highly suitable animal model for DMD, particularly with regard to potential therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…19 In DMD and CXMD, skeletal muscle shows early fiber necrosis and regeneration, associated with perimysial and endomysial connective tissue proliferation. 20,21 CXMD is therefore a highly suitable animal model for DMD, particularly with regard to potential therapeutic approaches. Correction of the consequences of dystrophin deficiency by gene transfer in the canine model should help us to develop a similar treatment strategy in DMD.…”
Section: Introductionmentioning
confidence: 99%